Diversity and use of the medicinal flora of the Cajamarca Region (Northern Peru): A compendium from 1988 to 2022. - Seminario, Juan F. (2024)
Information on the richness and use of medicinal plants in the Cajamarca Region (RC), Peru, was compiled and analyzed in 49 studies, carried out from 1988 to 2022. Botanical information, altitudinal distribution, endemisms, conservation categories and applications are presented. in groups of conditions, in traditional medicine. The medicinal flora of the RC includes 1115 species from 141 families, with a predominance of Asteraceae, Fabaceae, Lamiaceae and Solanaceae. The majority are herbaceous, native and wild, less than 20% cultivated and distributed mainly in the mesotropics. Ninetyone medicinal species endemic to Peru and 10 endemics exclusive to the RC were found. 59 species were registered within some category of threat and 18 in critical danger, according to national legislation. They have applications in 21 groups of conditions, with digestive and respiratory predominance. This compendium constitutes the baseline for monitoring medicinal species, in relation to conservation and climate change.